Factors that prevent prolonged breastfeeding in Basic Health Units in Guarulhos - Thaís Ferreira Bassan; Aline de Piano Ganen; Adriana Garcia Peloggia de Castro (O Mundo da Saúde, 2022)
Prolonged breastfeeding promotes several health benefits for the child, as well as for the mother, family, and society. Given this and the scarcity of studies on the aspects involved in the practice of breastfeeding after the sixth month of life, the present study aimed to discover the factors that make it difficult to maintain breastfeeding (from six monthx to two years or more). This was a cross-sectional study, carried out in four randomly selected basic health units located in the city of Guarulhos. The sample consisted of mothers and employees of the basic health units in question, with children aged between six and twenty-four months old. For data collection, two informative questionnaires with the study variables were used. Simple and multiple regression analyses were used to investigate associations between variables. The use of a bottle and a pacifier were important factors for the interruption of prolonged breastfeeding. However, in the adjusted analysis, maternal age predisposes them to interrupt of prolonged breastfeeding. According to the multiple logistic regression model, the use of a pacifier increases the chance of not maintaining prolonged breastfeeding by almost 20-fold, and children who use a bottle have this chance increased by six-fold. It is concluded that the child aging, bottle use, and pacifier use were decisive factors for not maintaining prolonged breastfeeding. Returning to work and storing breast milk were identified as the main difficulties in maintaining breastfeeding.